Quitting behaviours and cessation methods used in eight European Countries in 2018: findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Papadakis, Sophia; Katsaounou, Paraskevi; Kyriakos, Christina N; Balmford, James; Tzavara, Chara; Girvalaki, Charis; Driezen, Pete; Filippidis, Filippos T; Herbeć, Aleksandra; Hummel, Karin; McNeill, Ann; Mons, Ute; et al.
Abstract: Background: We examined quit attempts, use of cessation assistance, quitting beliefs and intentions among smokers who participated in the 2018 International Tobacco Control (ITC) Europe Surveys in eight European Union Member States (England, Germany, Greece, Hungary, the Netherlands, Poland, Romania and Spain). Methods: Cross-sectional data from 11 543 smokers were collected from Wave 2 of the ITC Six European Country (6E) Survey (Germany, Greece, Hungary, Poland, Romania and Spain—2018), the ITC Netherlands Survey (the Netherlands—late 2017) and the Four Countries Smoking and Vaping (4CV1) Survey (England—2018). Logistic regression was used to examine associations between smokers' characteristics and recent quit attempts. Results: Quit attempts in the past 12 months were more frequently reported by respondents in the Netherlands (33.0%) and England (29.3%) and least frequently in Hungary (11.5%), Greece (14.7%), Poland (16.7%) and Germany (16.7%). With the exception of England (35.9%), the majority (56–84%) of recent quit attempts was unaided. Making a quit attempt was associated with younger age, higher education and income, having a smoking-related illness and living in England. In all countries, the majority of continuing smokers did not intend to quit in the next 6 months, had moderate to high levels of nicotine dependence and perceived quitting to be difficult. Conclusions: Apart from England and the Netherlands, smokers made few quit attempts in the past year and had low intentions to quit in the near future. The use of cessation assistance was sub-optimal. There is a need to examine approaches to supporting quitting among the significant proportion of tobacco users in Europe and increase the use of cessation support as part of quit attempts